Isolation and identification of Bifidobacterium species from human breast milk and infant feces in Indonesia - ROBIN DOSAN; SAMUEL OWEN MUDANA; CLARA MEIRINZHA PANG JULYANTO; EMILY TANIA PURNAMA; MARCELIA SUGATA; JUANDY JO; TJIE JAN TAN (Society for Indonesian Biodiversity, 2024)
Abstract. Dosan R, Mudana SO, Julyanto CMP, Purnama ET, Sugata M, Jo J, Tan TJ. 2024. Isolation and identification of Bifidobacterium species from human breast milk and infant feces in Indonesia. Biodiversitas 25: 337-343. There has been a growing interest in identifying emerging probiotic strains because of their benefits for human health. Many bifidobacteria originated from humans have been reported to possess probiotics properties. They are commonly found in the intestine of breast-fed infants. Hence, this study aimed to isolate and identify bifidobacteria from human breast milk and infant fecal samples in Indonesia and evaluate their probiotic properties. Twenty colonies were isolated from two independent fecal samples and two independent breast milk samples. Ten isolates (BR1-M1, BR1-B1, BR2-5, BR2-6, BR2-12, BS2-PB3, BS2-PB5, BS2-PS1, BS2-PS2, BS2-MB1) showed a compatible phenotypic character with Bifidobacteria based on the Bergey’s Manual, including Gram-positive, irregular rods, no catalase activity, non-spore-forming, and non-motile. Subsequently, four isolates with similar carbohydrate fermentation patterns as Bifidobacterium spp. were selected for further molecular identification based on 16S rRNA gene sequencing analysis. The results showed that BR2-5 and BR2-6 were found to be closely related to Bifidobacterium animalis subspecies lactis with 100 and 98.39% similarity, respectively. Meanwhile, BS2-PS1 and BS2-PB3 were found to be closely related to Bifidobacterium breve with 100 and 98.26% similarity, respectively. Further investigation revealed that BR2-5 and BS2-PB3 were resistant to low pH (?4) and could tolerate the exposure of bile salts (1%). Both isolates survived under different oxidative stress conditions (aerobic and microaerophilic). In conclusion, BR2-5 and BS2-PB3 exhibited promising characteristics as probiotic candidates, though further investigations are required to substantiate these current findings.